2023
DOI: 10.3390/mi14101882
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Copper Nanoparticles with Medicinal Plants Extracts: From Extraction Methods to Applications

Aurora Antonio-Pérez,
Luis Fernando Durán-Armenta,
María Guadalupe Pérez-Loredo
et al.

Abstract: Copper nanoparticles (CuNPs) can be synthesized by green methods using plant extracts. These methods are more environmentally friendly and offer improved properties of the synthesized NPs in terms of biocompatibility and functional capabilities. Traditional medicine has a rich history of utilization of herbs for millennia, offering a viable alternative or complementary option to conventional pharmacological medications. Plants of traditional herbal use or those with medicinal properties are candidates to be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 175 publications
0
3
0
Order By: Relevance
“…Many reports of antibacterial, antifungal, larvicidal, anti-termite [ 61 , 62 , 63 , 64 , 65 ], and anticancer [ 66 , 67 ] activities of CuONPs derived from plants, animals, and microorganisms. Furthermore, several studies conducted in recent years have demonstrated the advantages of employing snail mucus to synthesize Ag and AuNPs, which have been shown to have broad-spectrum antibacterial activity, anticancer potential, and anti-inflammatory properties [ 21 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many reports of antibacterial, antifungal, larvicidal, anti-termite [ 61 , 62 , 63 , 64 , 65 ], and anticancer [ 66 , 67 ] activities of CuONPs derived from plants, animals, and microorganisms. Furthermore, several studies conducted in recent years have demonstrated the advantages of employing snail mucus to synthesize Ag and AuNPs, which have been shown to have broad-spectrum antibacterial activity, anticancer potential, and anti-inflammatory properties [ 21 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…A concentrated extract was created by cooling the liquid extract after extraction and using a rotary evaporator to concentrate the solvent content. [11][12][13] The method for isolating and purifying bioactive compounds is as follows: [14][15][16][17] Extraction This is the initial step where solvents extract bioactive compounds from the natural source material. Different solvents can be used depending on the targeted compounds' properties.…”
Section: Extraction Process and Isolation Of Phytoconstituentsmentioning
confidence: 99%
“…Ephedra alata leaves contain various phytochemicals, including flavonoids, alkaloids and phenolic compounds. These leaves have been used as reducing and capping agents for the synthesis of gold, silver, and copper oxide NPs ( Mousavi et al, 2018 ; Al-Radadi, 2023 ; Antonio-Pérez et al, 2023 ; Atri et al, 2023 ; Bouzid et al, 2023 ). Therefore, Ephedra alata extracts could be used for NP production in order to address the concerns associated with the very high toxicity of conventional NP production systems that poses risks to human and animal health.…”
Section: Introductionmentioning
confidence: 99%